2015
DOI: 10.2134/jeq2014.02.0091
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Use of Nutrient Management: Lessons from Watershed Case Studies

Abstract: Nutrient enrichment of water resources has degraded coastal waters throughout the world, including in the United States (e.g., Chesapeake Bay, Gulf of Mexico, and Neuse Estuary). Agricultural nonpoint sources have significant impacts on water resources. As a result, nutrient management planning is the primary tool recommended to reduce nutrient losses from agricultural fields. Its effectiveness requires nutrient management plans be used by farmers. There is little literature describing nutrient management deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 33 publications
1
59
0
Order By: Relevance
“…They indicated that financial incentives and more readily available evidence to demonstrate effective local pollution reduction would have the greatest effect on adoption rates. Based on several farm surveys in North Carolina and a survey of farmers in 13 watersheds across the US, Osmond et al (2014) showed that farmers generally did not fully apply nutrient management plans or follow basic soil test recommendations even when they had them. Farmers were found to be hesitant to apply N at university-recommended rates because they did not trust the recommendations, viewed abundant N as insurance, or used recommendations made by fertilizer dealers.…”
Section: Socio-economic Impediments To Adopting the 4rsmentioning
confidence: 99%
See 2 more Smart Citations
“…They indicated that financial incentives and more readily available evidence to demonstrate effective local pollution reduction would have the greatest effect on adoption rates. Based on several farm surveys in North Carolina and a survey of farmers in 13 watersheds across the US, Osmond et al (2014) showed that farmers generally did not fully apply nutrient management plans or follow basic soil test recommendations even when they had them. Farmers were found to be hesitant to apply N at university-recommended rates because they did not trust the recommendations, viewed abundant N as insurance, or used recommendations made by fertilizer dealers.…”
Section: Socio-economic Impediments To Adopting the 4rsmentioning
confidence: 99%
“…Exceptions to these patterns have been noted when education, technical support, and funding resources focused on nutrient management included easing management demands, actively and consistently working directly with a small group of farmers, and providing both significant resource allocations to fund agency personnel and cost-share funds to farmers (Osmond et al 2014). A significant disconnect exists between farmer behavior relative to nutrient management and its importance as the first line-of-defense in reducing agricultural nonpoint source pollution.…”
Section: Socio-economic Impediments To Adopting the 4rsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the study reveals that the NO 3 -mitigation methods had some effectiveness at the farm scale but had little acceptance socially and would have to be implemented on a grand scale to be effective. Osmond et al (2015) synthesized results from informant surveys in 13 watersheds of the USDA Conservation Effects Assessment Project (CEAP) study, supplemented with field surveys from three nutrient-impaired watersheds in North Carolina. The CEAP results indicate that farmers generally did not follow nutrient management plans or basic soil test recommendations even when they had them.…”
Section: Insights From Social Science Studiesmentioning
confidence: 99%
“…To date, CEAP's field studies have not yet been able to determine how river basin water quality variations can be attributed to specific conservation farming practices within the studied watersheds (Tomer and Locke, 2011). On the other hand, CEAP projects have made significant progress in understanding and demonstrating how agricultural practices could be managed to reduce nitrate and phosphorus water pollution in environmentally sensitive rivers and estuaries (e.g., Mississippi River Basin and Chesapeake Bay; Lund et al, 2011;Osmond et al, 2015). The USDA's continued support of CEAP's field research, farmer education and encouragement of innovation (e.g., the NRCS Environmental Quality Incentives Program assistance to farmer investments in improved practices) is needed to build a better, more accurate knowledge base of how watershed ecosystem services function; and how they could be better protected, managed and valued.…”
Section: Ecosystem Services Issues: Landscape Scale and Watershed Manmentioning
confidence: 99%